In Vitro and In Vivo Establishment of Pasteurella Haemolytica A2 in the Lungs of Goats - Mat Amin, Maswati (1998)

(untitled)
Pneumonic pasteurellosis is an important respiratory disease of sheep and goats throughout the world. It is mainly caused by Pasteurella haemolytica even though Pasteurella multocida has occasionally been associated with the same disease. In vitro challenge of lung tissues with Pasteurella haemolytica A2 revealed an early colonization of the bacteria onto the lung tissue as early as 1 hour post-challenge. The severity of colonization increased with time of challenge and reached a maximum rate at 6 hours post-challenge . Similar in vitro challenge on the lung tissues derived from goats that were exposed earlier to intranasal sprays of formalin-killed Pasteurella haemolytica A2, however, revealed a less severe colonization by 6 hours postchallenge. Following intratracheal challenge of goats with 108/ml colony forming units of Pasteurella haemolytica A2, 20% of the goats succumbed to peracute infection in which they died within 12 hours post-challenge. Examinations of the lungs revealed classical toxaemic lesions consisted of severe pulmonary oedema, pulmonary congestion and haemorrhage, and thrombosis with a few neutrophils in the alveoli. The lesions were remarkably similar to those peracute infections caused by Pasteurella multocida types A and D. The only difference was the absence of Pasteurella haemolytica A2 organisms in the heart blood samples compared to the infections by Pasteurella multocida types A and D. Goats that survived the peracute episode developed pneumonic lesion. Phagocytic activity by the bronchoalveolar macrophages was obvious by 4 days postchallenge and by day 7 post-challenge, the goats which were unable to phagocytose most of the bacterial cells succumbed to severe pneumonia in which the bacteria proliferated and overloaded the lungs leading to the invasion of the bacteria into the pneumocytes and spreading the infection further. Goats with efficient phagocytosis were able to reduce the number of bacterial cells in the lungs leading to failure of bacterial establishment in the lungs. Infections by Pasteurella haemolytica A2 isolated from nasal mucosa produced an insignificantly (p>0.05) less extensive lung lesions compared to infections by Pasteurella haemolytica A2 isolated from pneumonic lungs. The pulmonary responses and pattern of lesion developrrient, however, remained similar for both isolates.